Knowledge of pediatricians and the importance of interdisciplinarity in attention to oral health in early childhood (Acta Scientiarum. Health Sciences, 2017)
The objective of this study was to evaluate the knowledge of pediatricians on the integrality of attention to oral health in early childhood. A cross-sectional study was conducted with a sample consisting of 70 doctors, working in public and private services, in the city of Belém, state of Pará, Brazil. Data were collected using a questionnaire with approaches on: the professional profile; the knowledge of oral health of children; the use of fluoride; and self-perception on knowledge of oral health. A descriptive analysis of the data was performed, and the association between variables was verified with the Chi-square test, with p = 0.05. The average age of respondents was 41 years. Most professionals were females (88.57%) and featured more than 20 years of professional experience (38.57%). In general, most pediatricians answered satisfactorily the questions related to knowledge of children's oral health. However, when questioned about the knowledge of the use of fluoride, most professionals (92.86%) presented outdated knowledge that could result in inappropriate conduct. It was concluded that most pediatricians have knowledge of oral health promotion, although some concepts and conducts should be updated, especially the importance of fluorides in the control of tooth decay.